Liturgia zakonna pomocą w rozwoju wiary i rozeznania powołania dla młodzieży - Lamorski, Oktawiusz Marcin (Studia Pastoralne, 2026)
Pope Francis, concerned about the future of the young people has summoned the Ordinary General Assembly of the Synod of Bishops devoted to the young people that will be held in October 2018. In the Preparatory Document he has invited, among others, the consecrated people to work with him and try to answer the important questions: How to help young people to meet Jesus? How to help them to develop their faith and discern their vocation? It seems that nuns, friars and monks may support the pastoral activity of the Holy Father by sharing the wealth of their community life. In this thesis, apart from the wealth of charisms and the heritage of the saint founders of religious congregations and orders the liturgical life of monasteries and convents has been especially underlined. New appreciation of the monastic liturgy by the ongoing formation as well as opening the liturgy, usually locked in monastic enclosure, to the young people, is a precious contribution to the evangelization. Therefore the author of the thesis focuses on silence, praying the Liturgy of Hours, the Holy Mass of the communities, the liturgical books and calendars and the ceremonies that accompany entering particular stages of monastic formation. It all constitutes the wealth, which the consecrated people living in cloisters, following the example of Mary of Bethany, want to present anew to the young people in the evangelic way. They want to do all of that in order for the young people to be able to recognize the God in the beauty of monastic liturgy, to believe in Him more deeply, and o discern where He wants to send them.